Theory of change for the pork value chains in Uganda developed for the CGIAR Sustainable Animal and Aquatic Foods Science Program - Ouma, Emily A.; Galie, Alessandra; Moodley, Ashnee; Lukuyu, Ben A.; Cook, Elizabeth A.J.; Rao, E.J.O.; Achandi, Esther; Baltenweck, Isabelle; Thomas, Lian F.; Dione, Michel M.; Ngwili, Nicholas; Leitner, Sonja; et al. (International Livestock Research Institute, 2025)
Since 2012, CGIAR and its partners have collaborated with stakeholders in Uganda's pork system to address constraints in the value chain, amidst the growing demand for pork. The constraints included farmers’ lack of knowledge of good breeding practices, poor access to quality, cost-effective feed rations- leading to low pig productivity; weak, decentralized veterinary structures at the district level that hampered the control and surveillance of diseases such as African swine fever; poor access to reliable pork markets, and lack of coordination along the value chain.